Pengembangan Islam Asia Tenggara Dalam Perekonomian Negara: Development of Southeast Asian Islam in the Country's Economy - Ni’mah, Ummi Lathifatun (Institut Agama Islam Sunan Giri Ponorogo, 2022)
The arrival of Islam in countries in Southeast Asia was almost all preceded by interactions between the people in the archipelago with Arab traders, India, Bengal, China, Gujarat, Iran, Yemen and South Arabia. In the 5th century BC the Malay Archipelago had become a stopover for traders who sailed to China and they had established relationships with the communities around the coast. This kind of condition is used by Muslim traders who stop by to spread Islam to residents around the coast. The writing of this paper seeks to discuss the problems surrounding; How did Islam enter the archipelago? What theory is the basis for the entry of Islam into the Archipelago How is the development of Islam in the archipelago?, so the writing of this paper aims to; Knowing the beginning of the entry of Islam into the archipelago, Knowing the basic theory of the entry of Islam into the archipelago, Knowing and understanding the development of Islam in the archipelago. Kedatangan Islam di negara-negara yang berada di Asia Tenggara hampir semuanya didahului oleh interaksi antara masyarakat di wilayah kepulauan dengan para pedagang Arab, India, Bengal, Cina, Gujarat, Iran, Yaman dan Arabia Selatan. Pada abad ke-5 sebelum masehi Kepulauan Melayu telah menjadi tempat persinggahan para pedagang yang berlayar ke Cina dan mereka telah menjalin hubungan dengan masyarakat sekitar pesisir. Kondisi semacam inilah yang dimanfaatkan para pedagang Muslim yang singgah untuk menyebarkan Islam pada warga sekitar pesisir. Penulisan makalah ini berusaha membahas permasalahan seputar; Bagaimana Islam masuk ke Nusantara? Teori apa yang menjadi dasar masuknya Islam ke Nusantara Bagaimana perkembangan Islam di Nusantara?, sehingga penulisan makalah ini bertujuan untuk; Mengetahui awal masuknya Islam ke Nusantara, Mengetahui teori dasar masuknya Islam ke Nusantara, Mengetahui dan memahami perkembangan Islam di Nusantara.